PENGARUH ATRAKTOR TALI RAFIA DAN PITA POLYPROPYLENE TERHADAP KOMPOSISI JENIS DAN KEHADIRAN IKAN PADA RUMAH IKAN DI TELUK AMBON - Randy Fauziyanto; Haruna Haruna; Kedswin G. Hehanussa; Julian Tuhumury (Universitas Pattimura, 2024)
This research aimed to investigate the impact of attractor materials on the species composition and presence of fish around fish houses. The study took place in Teluk Ambon Dalam, specifically in Rumah Tiga Village, Teluk Ambon Dalam District (Figure 1), over a period of 2 months from September to November 2022. The visual method was employed, involving direct observations of fish houses equipped with either raffia rope or Polypropylene Ribbon attractors. The most commonly associated fish species were Apogon moluccensis, with 172 found on raffia ropes and 153 on Polypropylene ribbons; followed by Aeoliscus strigatus, with 129 on raffia ropes and 110 on Polypropylene ribbons. The least associated species were Abudefduf lorenzi, with 15 found on raffia ropes and 14 on Polypropylene ribbons. The study concluded that the choice of attractor material did not significantly affect the composition or presence of fish